Predicting the temperature and strength development within cemented paste backfill structures - Fall, M.; Nasir, O. (Paste 2010: Proceedings of the Thirteenth International Seminar on Paste and Thickened Tailings, 2010)
In this paper, a thermo–chemo–mechanical (TCM) model is developed and implemented into FLAC software for predicting the strength development and distribution within hydrating cemented paste backfill (CPB) structure, temperature development and distribution within the CPB structures, heat transfer between CPB structures and mine rock temperatures. The developed model is validated against results from laboratory (on CPB samples and small scale model) and field studies of CPB. The validation tests show good agreement between the predicted and experimental laboratory and field results. The developed tool is then used to simulate the performance of CPB structure in several practical cases of mine backfill operations. From the simulation results valuable information was gained regarding the strength and heat development within CPB structures, the optimal curing time of a given CPB structure, the effect of filling rate and stope geometry of the strength and heat development within CPB structures, the effect of mix design (e.g. %binder, water content, initial mix temperatures, tailings types) on the performance (mechanical, thermal) of CPB structures. The developed tool will contribute to more cost-effective and safer design of CPB structures.